AUSTRALIAN AND NEW ZEALAND STUDY OF PHOTODYNAMIC THERAPY IN CHOROIDAL AMELANOTIC MELANOMA. Issue 5 (May 2020) - O'Day, Roderick F.; Pejnovic, Tanya M.; Isaacs, Tim; Muecke, James S.; Glasson, William J.; Campbell, William G.
Abstract : Purpose: To evaluate the safety and efficacy of primary photodynamic therapy (PDT) for posterior choroidal amelanotic melanomas. Methods: Patients with posterior choroidal amelanotic melanomas up to 6 mm in height were treated with PDT using verteporfin as the photosensitizing agent. Treatment was repeated every 3 months until the tumor was flat up to a maximum of 6 treatments. Tumor response and recurrence was assessed by clinical examination, photography, and ultrasonography. Patients were monitored 3 monthly for a minimum of 3 years. Results: Thirty-six of 41 (88%) patients had complete regression after an initial course of PDT. Of them, 20 (56%) had no recurrence, 3 (8%) had recurrences that were successfully treated with further PDT, and 13 (36%) had recurrences that failed or were not amenable to further PDT. None of the measured baseline characteristics predicted treatment outcomes. There was no reduction in visual acuity due to PDT. The mean follow-up time was 3.5 years. Conclusion: In this large series, primary PDT was highly effective in achieving initial regression of posterior choroidal amelanotic melanomas. Photodynamic therapy is a vision-preserving treatment option for these tumors; however, patients need to be followed up closely because there is a significant rate of recurrence. Abstract : Photodynamic therapy with verteporfin was used to treat posterior choroidal amelanotic melanomas with a tumor height of up to 6 mm. Primary photodynamic therapy was successful in 56% of patients at a mean of 3.5 years of follow-up with no detrimental impact on vision.